002 Special delivery: where best to take a head injured patient?. (14th September 2011) - Pickering, A; Cooper, K; Harnan, S; Sutton, A
Abstract : Objectives and Backgrounds: The current focus on development of specialist centres in the UK to improve outcomes is based on evidence from overseas care models. While care in a specialist neurosurgical centre will improve outcomes for head injured patients, does transferring them directly have any clinical benefit compared with delivery to a local hospital for initial stabilisation and subsequent transfer to the specialist centre? We performed a systematic review to identify the clinical effectiveness of bypassing local hospital care in moderate or severely head injured patients. Methods: Relevant studies were identified by an electronic search of key databases. Papers in English were included if they compared the outcomes of moderate or severely head injured patients (GCS<13, AIS≥3) directly transferred and treated at a specialist centre (SC) vs those who received their initial resuscitation at a local hospital (LH) with some or all patients later transferred to a SC. Outcomes were assessed using available mortality and morbidity data. Results: We identified 6 studies involving 2580 patients. One further study was found that did not report the number of subjects. Most studies used SC registry data and adjusted their outcomes for age, pupil dilatation and injury severity. No studies included results for, or adjusted for, patients not transferred after delivery to the LH. For mortality, the adjusted OR was taken from three studies. For those taken to their LH first the OR of death was higher than for the direct transfer group (SC). The level of significance was marginal and undergoing formal meta-analysis at the time of submission. The adjustment of data tended to favour direct transfer over local hospital delivery. No significant difference was reported for morbidity outcomes (Glasgow Outcome Scale) in the three studies that looked at these. Conclusions: The reviewed literature comparing direct transfer of head injured patients to specialist neurosurgical centres vs initial local hospital delivery is sparse. What evidence there is supports direct transfer to improve mortality although, at present, this is only marginally significant.